Investigating the Use of Speech Act of Suggestions of Turkish ELT Students (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
This paper outlines an attempt to research the speech act of suggestion of ELT students majoring at a state university in Turkey. A written discourse completion task (WDCT) and a semi-structured interview were used to collect data. The WDCT was developed by the researcher, and the responses of the participants were analyzed based on Martinez-Flor’s speech act of suggestion criteria. Regarding the participants' answers, it can be said that most of the participants used more conventionalized forms rather than the other forms. The data revealed that ‘direct strategies’ were the least used ones, but ‘hints’ were never used.  Moreover, gender and high school differences did not play a prominent role in the production of suggestion strategies. It is believed that the findings of this study will enlighten our knowledge to understand some Turkish EFL/ELT university students’ production and perception of the speech act of suggestion because most of the studies in the Turkish context were about either refusal or complaining strategies; therefore, this study is believed to fill in this gap in this area. Correspondingly, this present study will also pave the ground to reconsider some critical points regarding the gap in the literature.